SONOROUS POLLUTION BY VEHICLE IN JAVIER PRADO AVENUE - Santos De La Cruz, Eulogio (2007)
The sonorus pollution produced by the noise of vehicles is the factor that more annoyances causes to the urban population, the in habitants of Lima are exposed to this problem, it implies to know the problematic of the noise and it demands an enormous effort, being difficult to include all the city, for that reason it's focused on zones, choosing Javier Prado avenue by the East and the Brazil avenue by the West, making surveys to the passers-by and conductors in the rush hour 07:00 - 09:00 and 15:00 - 19:00 hours in the dense area of congestion to vehicular, to mitigate requires a good urban planning, optimal environmental desing of ways and with the suitable use of the ground will get a minimum impact of the noise.